2010
DOI: 10.1080/17470218.2010.486903
|View full text |Cite
|
Sign up to set email alerts
|

Simon-Like and Functional Affordance Effects with Tools: The Effects of Object Perceptual Discrimination and Object Action State

Abstract: In the present study two separate stimulus-response compatibility effects (functional affordance and Simon-like effects) were investigated with centrally presented pictures of an object tool (a torch) characterized by a structural separation between the graspable portion and the goal-directed portion. In Experiment 1, participants were required to decide whether the torch was red or blue, while in Experiment 2 they were required to decide whether the torch was upright or inverted. Our results showed that with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
112
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 37 publications
13
112
2
1
Order By: Relevance
“…Along with the finding in Experiment 1, the results suggest that the object-based correspondence effect is primarily driven by object location (the spatial-coding account; e.g., Bub & Masson, 2010;Cho & Proctor, 2010) rather than by the orientation of an object's grasping component (the object affordance account; Goslin et al, 2012;Iani et al, 2011;Pellicano et al, 2010;Tucker & Ellis, 1998).…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…Along with the finding in Experiment 1, the results suggest that the object-based correspondence effect is primarily driven by object location (the spatial-coding account; e.g., Bub & Masson, 2010;Cho & Proctor, 2010) rather than by the orientation of an object's grasping component (the object affordance account; Goslin et al, 2012;Iani et al, 2011;Pellicano et al, 2010;Tucker & Ellis, 1998).…”
Section: Methodsmentioning
confidence: 66%
“…The basic finding is that responses are faster when the correct response is on the same side as the handle (e.g., a left key response when the handle is oriented to the left) than when it is on the opposite side (e.g., Tucker & Ellis, 1998). This object-based correspondence effect has been attributed by many authors to a grasping affordance (the object affordance account; e.g., Iani, Baroni, Pellicano, & Nicoletti, 2011;Pellicano, Iani, Borghi, Rubichi, & Nicoletti, 2010;Tucker & Ellis, 1998). However, other authors have proposed instead that the effect is due primarily, if not entirely, to location coding similar to the coding that underlies the correspondence effects obtained for stimuli displayed in left and right locations (the spatial-coding account; e.g., Bub & Masson, 2010;Cho & Proctor, 2010; see also Bub, Masson, & Lin, 2013).…”
mentioning
confidence: 88%
“…This occurs when the handles of manipulable objects are presented such that they are more accessible to one hand or another, resulting in an enhanced response from the compatible hand, in terms of both reaction times and motor-evoked potentials (Buccino et al 2009;Tucker and Ellis 2004). This has been shown to not be just a Simon effect (i.e., faster right-hand responses for right visual-field stimuli and vice versa), but instead derives from the functional properties of the object (Buccino et al 2009;Makris et al 2011;Pellicano et al 2010). For instance, it does not hold if objects have broken handles that still extend towards the left or right but no longer afford a functional grasp (Buccino et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, Tipper et al (2006) were the first who showed that the affordance effect was modulated by the task, since it was present only when participants were required to categorize handles as to their shape, not to their color. In keeping with this result, Pellicano et al (2010) used torches and demonstrated that when categorizing them on the basis of color (blue vs. red), a Simon effect (compatibility between the goal-directed tip of the object and the location of the key to press to respond) was found, but no affordance effect was present. The affordance effect, intended as the compatibility between the position of the object handle (left, right) and the location of the key to press (left, right), was present only when participants had to decide whether a given torch was upright or reversed.…”
Section: Affordances Automaticity Questionedmentioning
confidence: 87%